Independence and Responsibility of Mass Media in Indonesia: The Sweetness and Bitterness of Freedom - Erman Anom; Yumelda Sari; Nurmala Nurmala (INJECT (Interdisciplinary Journal of Communication), 2025)
It is recognized that the press in Indonesia has not entirely implemented a professional and responsible press quality in reporting. This should be watched out for, considering that not all Indonesians have adequate education and intelligence levels. In this study, using the document analysis method and in-depth interviews, it was found that the press was allowed to run without control and responsibility, so this could potentially become a medium of agitation that could affect the psychology of the uneducated community, which, in fact, is greater in number than the educated community. Therefore, this study suggests that press freedom needs to be limited, at least through legal means and legislation. So that the news carried out by the press can become responsible and accountable press reporting. The first use of press freedom was in England 316 years ago. This use is a development of the concept of freedom of speech, which has its roots in Greece since the glorious days of the Romans and Greeks. Indonesia today is said to be practicing responsible press freedom. In terms of philosophy, the Indonesian press is not a responsible press freedom because the press is very free beyond freedom itself. To achieve responsible freedom of the press, several elements or other powers in society need to be given wider independence. The trick is to strengthen the four elements of the branch of power, namely the legislature (the people), the executive, the judiciary, and the press. On the other hand, the executive power, the legislative power that is the most powerful in the country today, needs to be balanced according to its function and should be limited or reduced, in line with the limited government principle, so that the system of mutual control, balance and does not bring down each other contained in the Constitution. And Pancasila becomes more meaningful. Empowering the elements of power based on the Pancasila ideology above will make Indonesia more open, the press more independent, and the freedom to have a wider voice. Its implementation involves and refers to the need for a press law by responding to the needs of the government, society, and the press itself; realize a social contract regarding the freedom of the press which is responsible between the government, the press, and the public; create a code of ethics for the press. Ideally, the idea of responsible press freedom should be implemented in Indonesia today. This idea will not weaken the government; on the contrary, it will strengthen democracy in this country.